Návrhy na zlepšení optimalizace pro vyhledávače e-shopu z hlediska obsahu - Pohanka, Pavel (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Diplomová práce se zabývá optimalizací pro vyhledávače e-shopu Czech Art z hlediska jeho obsahu. Práce se skládá ze tří částí, přičemž v první, teoretické části, jsou definovány teoretické poznatky z oblasti marketingu a SEO. Druhá, analytická část, je zaměřena na podrobnou analýzu současného stavu e-shopu a v poslední, návrhové části, jsou sepsány návrhy na zlepšení optimalizace e-shopu czech-art.com z hlediska jeho obsahu. Návrhy vycházejí z poznatků zjištěných v rámci analytické části práce.

The thesis focuses on search engine optimization (SEO) of the Czech Art e-shop. The work is divided into three parts. The first, theoretical part defines the theoretical background of marketing and SEO. The second, analytical part is devoted to a detailed analysis of the current state of the e-shop. Finally, the third, proposal part presents suggestions for improving the SEO of the website czech-art.com, particularly in terms of its content. The proposed improvements are based on the findings from the analytical section of the thesis.
Proposals for Improving Search Engine Optimization of E-shop in Terms of Content
Keywords: online marketing; optimalizace pro vyhledávače; výsledky vyhledávání; metapopisek; metatitulek; SEO; on-page SEO; off-page SEO; obsahový marketing; linkbuilding; obsahové SEO; marketingový mix na internetu; online marketing; search engine optimization; search engine result page; metadescription; metatitle; on-page SEO; off-page SEO; content marketing; linkbuilding; content SEO; marketing mix on internet